Tantangan dan Strategi Pengamanan di Lembaga Pemasyarakatan Kelas IIA Lombok Barat - Jagad, Suluhuddin Puji (Dialog Legal: Jurnal Syariah, Jurisprudensi dan Tata Negara, 2026)
This study aims to analyze the effectiveness of the security system at Class IIA West Lombok Correctional Facility, which faces multidimensional challenges. The research employed a qualitative method with a case study design. Data were collected through in-depth interviews with 15 informants (officers and inmates), participatory observation for 30 days, and documentation studies. The results revealed three key themes: (1) Severe infrastructure and human resource limitations, marked by 250% overcapacity and an officer-to-inmate ratio of 1:30, were the root cause of tension and hindered effective supervision; (2) The implementation of Dynamic Security, colored by the local wisdom of "Bethek," was effective in mitigating conflict but risked blurring formal regulations; (3) Technology adoption was hampered by low user acceptance due to inadequate training and technical obstacles. These findings conclude that the security system requires a contextual, integrated approach that harmonizes technical, human, and cultural aspects. This study recommends holistic steps, including capacity addition, the development of hybrid guidelines, and continuous training to create an effective and sustainable security environment.